The grammar cracker unlocking English grammar - ebrary, Inc.; Vocalis Ltd. ([Cambridge, England] : Vocalis, Ltd., 2001)
Presents the rules of English grammar, including word origins, parts of speech, sentence structure, punctuation, and writing styles.
Electronic reproduction.
Keywords: Computer games; English language -- Grammar -- Software; Electronic books